Re-Estimating the Impact of Natural Gas on Global Carbon Emissions: The Role of Technological Innovation - Dou, Yue; Zhao, Jun; Dong, Jiajia (Frontiers in Energy Research, 2021)
To investigate the nexus between natural gas consumption, global carbon dioxide (CO2) emissions, and technological innovation, this study employs a balanced panel dataset of 73 countries for the period 1990-2019 based on the fixed effect (FE) and random effect (RE) estimation methods. Considering potential heterogeneity in the natural gas-CO2 nexus, this study divides the 73 countries into regional comprehensive economic partnership (RCEP) countries and non-RCEP countries for comparative analysis. The main findings indicate that natural gas consumption can significantly promote CO2 emissions for the full sample and non-RCEP countries, and improved technological innovation can help alleviate CO2 emissions from natural gas consumption. In the RCEP countries, technological innovation can improve the carbon emission reduction effect of natural gas. Furthermore, economic growth and global CO2 emissions show an inverted U-shaped relationship, which confirms the environmental Kuznets curve (EKC) hypothesis. Finally, several policy implications are provided to reduce global CO2 emissions and promote green recovery in the post-epidemic era.